2021
DOI: 10.1037/edu0000625
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the links between rapid automatized naming (RAN), phonological awareness, and reading.

Abstract: It is well established that phonological awareness (PA) and rapid automatized naming (RAN) tasks reliably predict children's developing word reading abilities, across a wide range of languages. However, existing research has not yet demonstrated unequivocally whether RAN and PA are independently and causally linked to reading, nor fully explored the underlying cognitive mechanisms. Most existing research has assessed PA and RAN in children who may already have some reading skill, making direction of influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Instead, phonology and RAN accounted for most of the variance in reading accuracy. This aligns with studies that have shown both RAN and phonology play a predictive role in reading accuracy, in particular in the earliest stages of learning to read an alphabetic language (e.g., Powell & Atkinson, 2021;Yeung, 2016).…”
Section: Gen Er a L Discussionsupporting
confidence: 89%
“…Instead, phonology and RAN accounted for most of the variance in reading accuracy. This aligns with studies that have shown both RAN and phonology play a predictive role in reading accuracy, in particular in the earliest stages of learning to read an alphabetic language (e.g., Powell & Atkinson, 2021;Yeung, 2016).…”
Section: Gen Er a L Discussionsupporting
confidence: 89%
“…This is important because an observed association between early phonological awareness and later reading may be caused by only few precocious children who already have basic letter knowledge or reading skills at the first assessment (Castles & Coltheart, 2004). Powell and Atkinson (2020) recently reported an interesting longitudinal study with English-speaking children who were first assessed as early as age 3;11 years. Even at that early point in development, some children could already read simple words and were explicitly excluded from analysis.…”
Section: Phonological Awarenessmentioning
confidence: 99%
“…Indeed, in previous studies, the ID group has often been matched to TD children according to their verbal mental age ( Channell et al., 2013 ; Ypsilanti et al., 2006 ), and most existing research has assessed RAN skills in children who already have reading skills. This makes direction of influence hard to ascertain since skills such as PA or RAN are not only reading precursors but also develop under the influence of reading acquisition ( Perfetti et al., 1987 ; Powell and Atkinson, 2020 ). To prevent these issues, it is important to select and to match ID and TD children on the basis of low reading skills.…”
Section: Theorymentioning
confidence: 99%